2006
DOI: 10.1074/jbc.m605850200
|View full text |Cite
|
Sign up to set email alerts
|

Denmotoxin, a Three-finger Toxin from the Colubrid Snake Boiga dendrophila (Mangrove Catsnake) with Bird-specific Activity

Abstract: Boiga dendrophila (mangrove catsnake) is a colubrid snake that lives in Southeast Asian lowland rainforests and mangrove swamps and that preys primarily on birds. We have isolated, purified, and sequenced a novel toxin from its venom, which we named denmotoxin. It is a monomeric polypeptide of 77 amino acid residues with five disulfide bridges. In organ bath experiments, it displayed potent postsynaptic neuromuscular activity and irreversibly inhibited indirectly stimulated twitches in chick biventer cervicis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
152
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 66 publications
4
152
0
Order By: Relevance
“…Identification was further confirmed by N-terminal sequencing of the first 36 residues, which matched the cDNA sequence of the MTLP-3 homolog (20). This protein was found to be a homodimer (see below) and hence was renamed as haditoxin (O. hannah dimeric neurotoxin) following the nomenclature of dimeric 3FTxs (12,13).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Identification was further confirmed by N-terminal sequencing of the first 36 residues, which matched the cDNA sequence of the MTLP-3 homolog (20). This protein was found to be a homodimer (see below) and hence was renamed as haditoxin (O. hannah dimeric neurotoxin) following the nomenclature of dimeric 3FTxs (12,13).…”
Section: Resultsmentioning
confidence: 93%
“…Chick Biventer Cervicis Muscle (CBCM) Preparations-The CBCM nerve-skeletal muscle preparation (39) was isolated from chicks (6 days old) and mounted in the organ bath chamber under similar experimental conditions as described previously (12,31). The effect of haditoxin (0.05-5 M; n ϭ 3) or ␣-bungarotoxin (0.01-1.0 M; n ϭ 3) on nerve-evoked twitch responses of the CBCM were studied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, although the results indicated that the major PLA 2 eluted in peak 9 (which accounts for ~20% of the total venom proteins) was not lethal to mice, the possibility that this protein exhibits taxon-specific activity, as reported for other toxins [83][84][85][86][87], requires future detailed investigation. Finally, of relevance from a clinical standpoint, the sea snake antivenom manufactured by CSL in Australia using the venom of E. schistosa displays sufficient immunological cross-reactivity to provide protection from the lethal effects of P.…”
Section: Accepted M Manuscriptmentioning
confidence: 80%